A review of electrode materials for electrochemical supercapacitors - Wang, Guoping; Zhang, Lei; Zhang, Jiujun (Chemical Society reviews, 2012)
In this critical review, metal oxides-based materials for electrochemical supercapacitor (ES) electrodes are reviewed in detail together with a brief review of carbon materials and conducting polymers. Their advantages, disadvantages, and performance in ES electrodes are discussed through extensive analysis of the literature, and new trends in material development are also reviewed. Two important future research directions are indicated and summarized, based on results published in the literature: the development of composite and nanostructured ES materials to overcome the major challenge posed by the low energy density of ES (476 references).